The writing of violence in the Middle East inflictions - Mohaghegh, Jason Bahbak 1979- (Suspensions (Series), 2012)
From the domains of contemporary Middle Eastern literature, this book stages a conversation on questions of cruelty, evil, rage, vengeance, madness, and deception. It forms a record of voices, movements, and thought - experiments drawn from the inner circles of the Middle Eastern region